การพัฒนารูปแบบการพัฒนาคณาจารย์สถาบันอุดมศึกษาเอกชน - ขนิษฐา ทรงจักรแก้ว (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
The purposes of this research were 1) to do needs assessment for faculty development in Thai private higher education institutions 2) to propose an alternative for faculty development 3) to develop a faculty development model for private higher education institutions. Data on faculty development’ needs were collected from annual reports of 46 institutions and Self Assessment Report (SAR) of the 2550 academic year. To analyze those needs, concept mapping technique was used for the concept statements data which collected from 64 administrators and faculty members of 10 universities. Focus group of experts was used in developing the plausible scenario and propose faculty development solutions which underlined by the 8- group causes of faculty development’ needs. The model was tested with 10 faculty members from School of Business Administration at Eastern Asia University, together with the dean of the Faculty of Information Technology who serve as a mentor. Research findings of the most important needs for faculty development were to heighten academic position and develop the quality of the research mission. The most important causes of those needs, rating from 98-statement causes, in faculties’ and administrators’ points of view were the inappropriate benefit-oriented of some institutional leaders and the faculty’ lack of motivation to improve oneself, respectively. From 8-group causes, the faculties’ and administrators’ points of view were the policy, management and institutional leader and the compensation group, respectively. The findings of plausible future scenario were co-petition with quality and marketing. The two elements of desirable faculty development were maintenance and motivator. The four groups of maintenance element were 1) the policy, management and institutional leaders 2) the administrative system 3) the compensation 4) the environment and academic atmosphere. The four groups of motivator element were 1) goals and motivations 2) knowledge and skill 3) attitudes and recognitions and 4) time-spending of faculty members. The CHANGE FACULTY DEVELOPMENT model is composed of the following elements 1) the principle of the model 2) the structure of the components and contents 3) the implementation procedure based on Lewin’s change model which is composed of 3 stages including 1. unfreezing 2. changing and 3. refreezing, in order to change the self-development needs, integrate missions and create value from research-based academic works to society and the institution and 4) the results of model evaluation was tested by having the instructors do action research in their courses that used service learning as an instructional approach.